Hyperactivation of BDNF‐TrkB Signaling Cascades in Human Hypothalamic Hamartoma (HH): A Potential Mechanism Contributing to Epileptogenesis. (13th October 2014) - Semaan, Suzan; Wu, Jie; Gan, Yan; Jin, Yu; Li, Guo‐Hui; Kerrigan, John F.; Chang, Yong‐Chang; Huang, Yao
Summary Aims Although compelling evidence suggests that human hypothalamic hamartoma (HH) is intrinsically epileptogenic for gelastic seizures, the molecular mechanisms responsible for epileptogenesis within HH remain to be elucidated. The aim of this study was to test the hypothesis that hyperactivation of BDNF‐TrkB signaling pathways in surgically resected HH tissue is a possible mechanism for downregulation of KCC2 expression, which in turn underlies GABA‐mediated excitation within HH. Methods Activation of three major BDNF‐TrkB signaling pathways including MAPKs, Akt, and PLCγ1 were evaluated in surgically resected HH tissue (n = 14) versus human hypothalamic control tissue (n = 8) using combined methodologies of biochemistry, molecular biology, cell biology, and electrophysiology. Results Our data show that compared with hypothalamic control tissue, in HH tissue, (i) activation of TrkB and expression of mature BDNF are elevated; (ii) MAPKs (including ERK1/2, p38, and JNK), Akt, and PLCγ1 are highly activated; (iii) KCC2 expression is downregulated; and (iv) pharmacological manipulation of TrkB signaling alters HH neuronal firing rate. Conclusion Our findings suggest that multiple BDNF‐TrkB signaling pathways are activated in HH. They act independently or collaboratively to downregulate KCC2 expression, which is the key component for GABA‐mediated excitation associated with gelastic seizures.